Metode Audio-Lingual sebagai Strategi Pengajaran Bahasa Arab di Sekolah Menengah Pertama - Vicky Agung Nurtanio; Jihan Alhanin Choir (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
This study aims to explore the effectiveness of using the Direct Method in teaching Arabic grammar and communication at the elementary school level. The Direct Method is a language teaching approach that emphasizes the use of the target language directly without using the mother tongue as an intermediary. In this context, students are encouraged to actively participate in daily conversations, understand, and apply grammar through direct practice. This study employs a qualitative approach with observation, interviews, and document analysis as data collection methods. Participants in the study included students from grades 4 to 6 at an Islamic Elementary School in Indonesia. The results showed that the use of the Direct Method significantly improved students' oral communication skills in Arabic. Students also demonstrated an increased understanding of grammar through direct application in conversations and other classroom activities. Furthermore, the study found that the Direct Method could enhance students' motivation and confidence in using Arabic. Teachers also reported that this method made it easier for them to create an interactive and enjoyable learning environment. However, challenges such as students' limited vocabulary and difficulties in understanding complex grammatical concepts still need to be addressed.